Livestock exclusion from watercourses: Policy effectiveness and implications. Issue 106 (April 2020) - Kilgarriff, Paul; Ryan, Mary; O'Donoghue, Cathal; Green, Stuart; Ó hUallacháin, Daire
Highlights: Spatial database used to examine cost effectiveness of livestock exclusion at the field, farm level and national scale. Fencing watercourses on medium/high intensity farms is ∼20% more cost effective relative to less intensive farms. Clear spatial differential in the cost effectiveness of livestock exclusion. Theil index shows the majority of the variation in cost effectiveness occurs within areas rather than between. Farm size and shape and farmer characteristics are important determinants of cost effectiveness of fencing individual farms. Abstract: The deterioration of water quality in Ireland over the past thirty years and the nutrient losses from agriculture are of particular concern to policy makers. Agri-environmental schemes (AES) are designed to improve the environment and water quality. One of the more common AES measures is the exclusion of cattle from watercourses. Cattle exclusion provides a number of benefits such as reduction in nitrogen, phosphorus and sediment run-off, riverbank stability and improved vegetation cover and biodiversity. Using GIS methods a new national farm boundary spatial database SLIDE (Spatial Land Identification Database for Éire) is created utilising national administrative data and a spatial data storage model. This is the first examination of cattle exclusion and its cost effectiveness at the individual farm level across a national population of farms. Benefits are measured in the form of reduced in-stream faecal deposits. The spatial distribution of cost-effectiveness at the sub-catchment level highlights the differences between areas in terms of costs, benefits and extent. A cluster analysis is used to aggregate results. This information is utilised to undertake an ex-ante examination of the implications of a national policy to restrict cattle access to waterbodies for specific categories of farmers, under the EU Nitrates Directive. The analysis of the clusters show that due to the reduction of faecal deposition in watercourses, fencing on medium and high intensity farms is ∼20 % more cost effective relative to farms with lower livestock densities. This study makes an important contribution to the literature in broadening our understanding of the impacts of policy decision making at the individual farm level and also the costs and scale of AES measures at a national level.